The Influence Of Youtube Advertising And Brand Awareness On Buying Interest In Honda Scoopy Motorbikes At Pt Astra Motor Honda Cirebon Branch - Siti Nurlaela; Sony Sony Basrizal; Soesanty Maulany (Al-Makki Publisher, 2024)
The purpose of this study is to examine how brand awareness and YouTube advertising affect consumers' inclination to purchase Honda Scoopy motorcycles from the PT Astra Motor Honda Cirebon Branch. Utilizing a survey approach, quantitative research methodology is applied. Questionnaires were sent to 150 respondents who were considering purchasing Honda Scoopy motorcycles in Cirebon in order to gather data. According to the results of a regression analysis, creative and informative YouTube advertising has the ability to pique customers' interests and has a favorable and significant impact on purchase intention. Additionally, it has been demonstrated that brand awareness positively and significantly influences buy intention; this means that consumers' purchase intentions are higher when brand awareness is higher. In conclusion, brand awareness and YouTube advertising work together to significantly impact consumers' intentions to buy Honda Scoopy motorcycles in Cirebon. PT Astra Motor Honda is advised to continue to improve the quality of advertisements on YouTube and strengthen branding strategies to increase consumer buying interest.